Peran Sistem Informasi Manajemen dalam Pemasaran Asuransi Syariah di PT. Asuransi Jiwa Syariah Al-Amin - Nabila Salsabilah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
In today's increasingly fierce global competition, every organization must have the ability to innovate in the development of information systems. This is important to achieve company goals, increase its effectiveness, and maintain its competitiveness. Companies require continuous and ongoing changes in the development of technology and information systems. Similarly, management information systems in insurance marketing function by disseminating relevant information to the marketing department, thereby enabling them to make effective decisions in marketing operations. Factors such as pricing, packaging, new product development, distribution, media, and advertising play an important role in the overall success of a product. Management information systems certainly have an important role, including in Islamic insurance marketing. The role of Management Information Systems (MIS) in Islamic insurance marketing remains important. SIM helps manage information regarding customers, products, and transactions with sharia principles. This allows Islamic insurance companies to monitor product performance, analyze customer needs, and respond to market changes more effectively.